FOREST ECOSYSTEM SERVICE UTILIZATION TO INCREASE HUMAN HEALTH: FOREST THERAPY TRIALS IN TAMAN HUTAN RAYA IR DJUANDA - Emmelinda Satyawan, Verda; Rusdiana, Omo; Latifah, Melly (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
Forest therapy is an activity used to obtain health benefits from forest environmental services. This research conducted a systematic literature review, constructed a forest therapy program based on said literature review, and experimented on how the forest therapy program affects human health. The forest therapy program was experimented with in